Body fat - based weight norms for children and youths - Joanna Głogowska; Małgorzata Lichota; Jan Czeczelewski; Katarzyna Milde; Paweł Tomaszewski; Romuald Stupnicki (Pediatric Endocrinology, Diabetes and Metabolism)
Introduction: The issue of establishing reference values, especially of those pertaining to somatic features, is of importance for an assessment of normal growth. It was assumed that norms ought to reflect not the actually existing status but the recommended one. Thus, weight-height relations, including body mass index (BMI), ought to be established for that fraction of the general population, in which body fat content is within physiologically acceptable limits. The aim of the study: To construct weight-to-height percentile norms for boys and girls aged 7-20 years. Material and methods: A cohort of healthy boys (n=1282) and girls (n=1150) attending schools in the Eastern regions of Poland participated in the study. Their body height, body mass and body fat content were determined, the latter by skinfold (Slaughter’s method) or bioimpedance measurements. The data for constructing normal values of body fat content were compiled from diverse sources so as to associate them smoothly with the normal values for adults. Results: By applying the proposed lower and upper limits of body fat, 1007 boys (78.5%) and 581 girls (50.5%) with acceptable fat content were selected for constructing percentile norms of body mass expected for height, as well as for BMI. Conclusions: The existing norms for BMI of children and youths, also the Polish ones, differ from each other, as these were not based on data from subjects with acceptable body fat and assessing body fat content from BMI is known to be markedly biased. Unlike BMI, the presented percentile weightfor-height norms are age-independent in the range 7-20 years and are thus much easier to use. Those norms may be recommended as a tool in assessing the course of normal growth, as well as in developmental disorders and possible clinical intervention.